Effect of waste tyre particles reinforcement on mechanical properties of jute and abaca fiber- epoxy hybrid composites with pre-treatment. (2021) - Yogeshwaran, S.; Natrayan, L.; Udhayakumar, Gobikrishnan; Godwin, G.; Yuvaraj, L.
Abstract: Composite manufacturing is the novel branch of science, which finds its immense applications in various industries such as sporting, automotive, aerospace and marine industries. The superior properties of composites such as stiffness, better mechanical properties, low density, and light weight make it a candidate in engineering applications. The need for seeking alternate materials with increased performance in the field of composites revived this research, to prepare the Jute and Abaca fiber with tyre particles reinforcement hybrid composites by hand layup method. The resin used in the preparation of composites was epoxy. The different five proportion of fiber and matrix material such as 80:0:20, 50:30:20, 40:40:20, 30:50:20, 0:80:20 without any pretreatment and were taken as the base line reference. Subsequently the tests have conducted on the above fibers with alkali treatment and tyre particles with H2 SO4 treatment to enhance the mechanical properties. Reused tyres particle was also used as reinforcement in epoxy matrix and this particle was treated with to improve ability of rubber to interact with epoxy, increasing stiffness and tensile strength. The jute fiber, abaca fiber and tyre particle were prepared with various weight ratio and then incorporated into the epoxy matrix. Samples prepared were tested to evaluate its mechanical properties such as tensile strength, flexural strength, and impact strength.